Hydroxytyrosol magnetic molecularly imprinted polymers as the sorbent for solid-phase extraction for selective recognition of hydroxytyrosol from Chinese olive leaves. (December 2021) - Yu, Qianqian; Gan, Hongxia; Feng, Nan; Li, Yuanfei; Han, Yongping
Abstract: As a by-product of Chinese olive, an important economic tree, Chinese olive leaves have a large amount of hydroxytyrosol and other ingredients with high biological activity. At present, Chinese olive leaves can only be treated as waste and animal feed, causing a lot of waste of resources and pollution to the environment. Magnetic molecularly imprinted polymers using hydroxytyrosol as a template molecule were synthesized by surface imprinting molecular technology. Several ways, such as X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope and vibrating sample magnetometer, were used to perform physicochemical characterization of Fe3 O4 @MIPs. The results of the kinetic and static adsorption experiments showed that adsorption equilibrium could be reached within 45 min, with a maximum adsorption capacity of 36.27 mg g -1 . Fe3 O4 @MIPs had good selectivity and specificity for hydroxytyrosol. Under the optimum conditions, an efficient method based upon MISPE combined with high-performance liquid chromatography (HPLC) was developed for the determination of hydroxytyrosol in Chinese olive leaves with the high recovery rate (96.71–98.06%) and relative standard deviations of 2.35–3.27%. Therefore, this research provided a new method for the separation, purification and determination of hydroxytyrosol from Chinese olive leaves, improved the resource utilization of Chinese olive leaves, and protected the environment. Graphical Abstract: ga1 Highlights: A new method was provide for the separation, purification and determination of hydroxytyrosol. Fe3 O4 @MIPs had high adsorption capacity and good selectivity for hydroxytyrosol. MISPE-HPLC had been successfully applied to the extraction and determination of hydroxytyrosol in olive leaves. Purified by MISPE column, the purity of the obtained hydroxytyrosol was above 96%.